2013
DOI: 10.3389/fpls.2013.00100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of nuclear proteome: extending its function

Abstract: Organeller proteomics is an emerging technology that is critical in determining the cellular signal transduction pathways. Nucleus, the regulatory hub of the eukaryotic cell is a dynamic system and a repository of various macromolecules that serve as modulators of such signaling that dictate cell fate decisions. Nuclear proteins (NPs) are predicted to comprise about 10–20% of the total cellular proteins, suggesting the involvement of the nucleus in a number of diverse functions. Indeed, NPs constitute a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 94 publications
(125 reference statements)
1
24
0
1
Order By: Relevance
“…Cushman, 1995;Zhang et al, 1995;Abdalla et al, 2009Abdalla et al, , 2010Sikorskaite et al, 2013], and root meristem [Silva et al, 2010], and in in vitro cultured cells [Willmitzer and Wagner, 1981]. Currently used extraction protocols directed at nuclear proteins use mechanical homogenization, filtration to remove large detritus, pelleting, suspension in a non-ionic detergent, and finally separation by density gradient centrifugation [for review see Narula et al, 2013]. This sort of scheme has provided descriptions of the Arabidopsis thaliana [Bae et al, 2003;Jones et al, 2009], hot pepper [Lee et al, 2006], rice [Tan et al, 2007;Li et al, 2008;Aki and Yanagisawa, 2009;Choudhary et al, 2009], barrel clover [Repetto et al, 2008], maize [Casati et al, 2008], black-stick lily [Abdalla et al, 2010;Abdalla and Rafudeen, 2012], soybean [Cooper et al, 2011], flax [Renouard et al, 2012], and chickpea [Pandey et al, 2006;Varshney et al, 2013] nuclear proteomes.…”
mentioning
confidence: 99%
“…Cushman, 1995;Zhang et al, 1995;Abdalla et al, 2009Abdalla et al, , 2010Sikorskaite et al, 2013], and root meristem [Silva et al, 2010], and in in vitro cultured cells [Willmitzer and Wagner, 1981]. Currently used extraction protocols directed at nuclear proteins use mechanical homogenization, filtration to remove large detritus, pelleting, suspension in a non-ionic detergent, and finally separation by density gradient centrifugation [for review see Narula et al, 2013]. This sort of scheme has provided descriptions of the Arabidopsis thaliana [Bae et al, 2003;Jones et al, 2009], hot pepper [Lee et al, 2006], rice [Tan et al, 2007;Li et al, 2008;Aki and Yanagisawa, 2009;Choudhary et al, 2009], barrel clover [Repetto et al, 2008], maize [Casati et al, 2008], black-stick lily [Abdalla et al, 2010;Abdalla and Rafudeen, 2012], soybean [Cooper et al, 2011], flax [Renouard et al, 2012], and chickpea [Pandey et al, 2006;Varshney et al, 2013] nuclear proteomes.…”
mentioning
confidence: 99%
“…1). These processes are related to the main functions of the nucleus, such as gene expression, transcriptional control, splicing, and release of gene products [10]. …”
Section: Resultsmentioning
confidence: 99%
“…The nucleus is the largest organelle of most cells and occupies approximately 10% of its volume, although this varies according to the cell type [9]. The nucleus is the compartment where the genetic material of eukaryotic organisms is stored, and nuclear proteins constitute 10-20% of the total cellular proteins and exert important functions related to gene expression, transcriptional control, splicing, and generation of the final gene products [10]. Therefore, the importance of investigating the nuclear proteome for the understanding of any physiological or pathological process is clear, and few such studies have been carried out thus far in the field of psychiatric disorders such as SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Organ level proteomics [200][201][202] ). These studies identified 91 proteins from total element of the cell, whereas 388 proteins were identified from the ECM, 479 proteins were identified from the nucleus and 91 proteins were identified from the membrane.…”
Section: The Current Status Of Proteomics In Chickpeamentioning
confidence: 99%